Millennial E-Wom Decisions: Investigation Of The Roles Of Partners, Internet, and Gender - Siti Asriah Immawati; Arief Bowo Prayoga Kasmo (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2023)
The aim of this paper is to find out the influence of the millennials in deciding their purchases through the eWom platform based on the role of peers, the duration of internet use, and gender. The research design is cross-sectional. Around 300 respondents from Indonesia participated in a self-managed survey who had experience using eWom in e-commerce buying local fashion clothes brands online. The study applied PLS-SEM to test the proposed model. Information from peers has been found to have a positive influence on the use of e-WOM. Internet usage positively affects consumer purchasing intentions. Usability perceived by consumers affects the use and purchasing intent of consumers. Gender also influences consumer purchasing intentions.